Applications of plant growth promoting regulators and nutrients in the enzyme activity of sugarcane and sugarbioenergy production - Hervatin, Cleber de Morais [UNESP] (2023)
The production of sugarcane is of global importance due to the high technology used and the supply of sugar, ethanol and biomass for energy production. One of the biggest challenges to reach high productivity is the unfavorable edaphoclimatic conditions, significantly reducing the productivity and quality of sugarcane. The expansion of sugarcane occurred in areas where the soils are limited in nutrients, as well as the predominance of adverse climates that negatively influence the culture to explore all its genetic potential. The foliar application of nutrients and plant regulators constitute an alternative to stimulate the primary and specialized metabolism of the plant, stimulating both the photosynthetic process and the defense system in mitigating possible biotic and abiotic stresses, consequently, a greater balance of photosynthesis, thus increasing productivity of sugar cane. The primary objective of these experiments was to understand how the supply of nutrients and plant regulators via foliar spraying could stimulate photosynthesis, the activity of antioxidant enzymes, greater productivity, quality and bioenergy. In this context, fifteen experiments were carried out with foliar applications containing in (mg l-1) with 17 of GA3, 820 of IAA and 43 of zeatin (Experiments RP) and seventeen experiments with foliar applications of fertilizers whose concentration in (g ha-1) was 330.0 of N, 260.0 of B, 12.0 of Cu, and 300.0 of Zn associated with plant regulators containing in (mg ha-1) 25 of indolebutyric acid, 25 of gibberellic acid and 45 of kinetin (FRP experiments) conducted during four consecutive harvests (2017-2018 , 2018-2019, 2019-2020 and 2020-2021), and in three sugarcane harvest seasons [beginning (May-July), middle (July-September) and end (November-December) of the harvest]. Foliar applications of plant regulators alone or associated with fertilizers were carried out in two stages, vegetative and maturation: Chapter 1 (RV) - (I) control, without foliar application of plant regulators (Control), (II) foliar application of regulators plants in the vegetative phase of sugarcane (V), (III) foliar application of plant regulators in the vegetative and maturation phase of sugarcane (VM). Chapter 2 (FRV) - (I) control, without foliar application of fertilizers associated with plant regulators (Control), (II) foliar application with fertilizer and plant regulators in the vegetative phase of sugarcane (V), (III) foliar application with fertilizer and plant regulators in the maturation phase of sugarcane (M), (IV) foliar application with fertilizer and plant regulators in the vegetative and maturation phase of sugarcane (VM). Both experimental models with foliar applications in (V and VM) promoted positive results for the photosynthetic enzyme phosphoenolpyruvate carboxylase (PEP; EC 4.1.1.31) and only (RV) resulted in increased activity of ribulose 1,5-bisphosphate carboxylase (Rubisco: EC4.1.1.39) when applied to V, M and VM, respectively. Lower values for malondialdehyde (MDA) and hydrogen peroxide (H2O2) and increased activity of the enzyme peroxidase (POD; EC 1.11.1.7), catalase (CAT; EC 1.11.1.6), ascorbate peroxidase (APX; EC:1.11.1.11) and proline concentration were observed in VM for both experimental models and superoxide dismutase (SOD; EC 1.15.1.1) in (FRV). There were increases in stalk diameter and length in (FRV) and stalk yield in both experimental models at the three harvest times in VM. The use of plant regulators alone or in combination with fertilizers in these studies promoted increases in the activity of photosynthetic and antioxidant enzymes, productivity and bioenergy, especially when performed in two seasons, in the vegetative stages and in maturation, confirming the proposed hypothesis.